Association between Sarcopenic Obesity Status and Nonalcoholic Fatty Liver Disease and Fibrosis - Wolhwa Song; Sung Hwan Yoo; Jinsun Jang; Su Jung Baik; Byoung Kwon Lee; Hyun Woong Lee; Jong Suk Park (Gut and Liver, 2023)
Background/Aims: There are no data regarding the association between sarcopenic obesity status and nonalcoholic fatty liver disease (NAFLD) and NAFLD-associated liver fibrosis. Therefore, we aimed to investigate the relationship between sarcopenic obesity status (sarcopenia only, obesity only, and sarcopenic obesity) and NAFLD and liver fibrosis in Korean adults.Methods: In total, 2,191 subjects completed a health checkup program, including abdominal ultrasonography and FibroScan. Subjects were classified into the following four categories: optimal body composition (nonobese and nonsarcopenic), sarcopenia only (nonobese), obesity only (nonsarcopenic), and sarcopenic obesity. Sarcopenic obesity was stratified by the skeletal muscle mass index and body fat using bioelectrical impedance analysis. NAFLD was diagnosed by ultrasonography, and liver fibrosis was assessed using transient elastography in subjects with NAFLD.Results: The prevalence of NAFLD and liver fibrosis significantly increased according to the sarcopenic obesity status. In the logistic regression analysis, after adjusting for multiple risk factors, the odds ratio (OR) for the risk of NAFLD was largest in the sarcopenic obesity group (OR, 3.68; 95% confidence interval [CI], 2.94 to 4.60), followed by the obesity only (OR, 2.25; 95% CI, 1.67 to 3.03) and sarcopenia only (OR, 1.92; 95% CI, 1.30 to 2.84) groups, when compared with the optimal group. Additionally, liver fibrosis was independently associated with sarcopenic obesity status (OR 4.69, 95% CI 1.95 to 11.29; OR 4.17, 95% CI 1.56 to 11.17; OR 3.80, 95% CI 0.86 to 16.75, respectively).Conclusions: These results demonstrated that sarcopenic obesity was independently associated with NAFLD and liver fibrosis and increased the risk of NAFLD and liver fibrosis more than obesity or sarcopenia alone.